The Time in which Drinks are Fermented Taken from Wines and Juices is a Comparative Juristic study (Islamic Sciences Journal, 2023)
This is a Jurisprudential research that examines the question of the time when fermentation of drinks taken from wines and juices, It is a comparative juristic study comparing the sayings of jurists, and the related legal provisions in terms of analysis, prohibition, permissibility and hatred    especially the drink is the lifeblood of all beings, the need for him to make some drinks that he enjoys is sweet, and that the juice of the good fruits that is discarded in water for a period of time, and then squeezed to drink greedily with its sweetness, which is permissible to use if these juices or the disc are just fresh. If I stayed until it intensified and boiled over, these drinks are the subject of a difference between jurists and scholars in the time to be avoided for fermentation and turning them into intoxicants, So the majority of jurists state that their prohibition is not related to the length of time, but the rule of prohibition is related to its corruption and its change from its state and the modern era witnessed by scientific development Now, the man realizes the composition of wine, and is able to extract the intoxicating and influencing substance with corruption, and he could prevent without creating it in juice and wine by adding some preservatives, or by cooling by keeping the juice in the coolers (refrigerators),Hence, and man is able to preserve the nature of the juices and wines for a long time that could reach several Months without spoiling or changing